Blacklist Elizabeth Keen's dossier - Bennett, Tara; Terry, Paul (Titan Books, 2016)
"Elizabeth Keen's Dossier is her detailed account of the world of The Blacklist. It contains a trove of in-world documentation, photographs, maps, newspaper cuttings and Liz's detailed notes on Red, Tom, each Blacklister, and the FBI agents she's meant to trust. This dossier unmasks Reddington's network, his connections and plans, and delves into the mysteries of Liz's own past, present and future"--Back cover
Keywords: Blacklist (Television program) / Handbooks, manuals, etc; Film